VARIASI BAHASA BIDANG EKONOMI DI ERA PANDEMI COVID-19 - ferdian achsani; Elen Inderasari; Farah Fauziyah Haqiqi; Siska Ayu Maharani (Kadera Bahasa, 2022)
AbstractThe purpose of this study is to describe the variety of languages in the Covid-19 pandemic era, especially in the economic field. This study uses a quantitative descriptive approach which will produce data in the form of descriptions of words instead of numbers. The form of diction or terms during the Covid-19 pandemic is the subject of this study. Meanwhile, the object of this research focuses on the characteristic patterns of various language terms in the economic sector in the Covid-19 pandemic era. This research technique uses observation techniques and data selection. This study provides results in the form of 51 data on the pattern of characteristics of various languages in the field of economic terms in the Covid-19 pandemic era and classified into 9 data in English, 8 data in synonym, 25 data in Indonesian abbreviation, 4 data in the form of language abbreviations. English, and 5 data in acronym form.Keywords: